Hukuman di Lingkungan Pendidikan Perspektif Hadist - Yogga Dwi Setyawan; Muhid (AL-IBROH: Jurnal Ilmu Pendidikan dan Keguruan, 2025)
Islamic education emphasizes not only the transmission of knowledge but also the development of noble character and moral discipline among students. One method used to instill discipline is punishment, which often sparks debate regarding its appropriateness in educational settings. This study aims to explore the concept of punishment in education based on the Hadith of Prophet Muhammad. The research employs a library research method with a descriptive-qualitative approach. Primary data sources include major hadith collections such as Sunan Abu Dawud and Sahih Muslim, supported by secondary literature in Islamic education and educational psychology. The findings indicate that punishment in Islam is not an act of violence but a form of ta’dib a nurturing process rooted in justice, compassion, and educational purpose. The Hadith provides ethical guidelines for administering punishment, emphasizing proportionality, non-violence, and character development. Thus, when implemented according to Islamic values, punishment can serve as an effective educational tool to foster holistic student growth both intellectually and spiritually.